2016
DOI: 10.2337/dc15-2723
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Women of Childbearing Potential in Clinical Trials of Type 2 Diabetes Medications: A Review of Protocol-Based Barriers to Enrollment

Abstract: OBJECTIVEWomen of childbearing potential are often excluded from participating in clinical trials owing to concerns about adverse fetal effects of treatment. This study aims to determine the prevalence of fertility-related exclusion criteria in clinical trials of type 2 diabetes medications and to determine whether these criteria are commensurate with drug risk.RESEARCH DESIGN AND METHODSClinicalTrials.gov was queried for trials of type 2 diabetes medications that were phase 2 or 3, were based in the U.S., and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…Similarly, even when not explicitly excluded, women remain under‐represented, in part due to fertility‐related exclusions. Although diabetes is a chronic condition with significant morbidity that affects men and women differently, nearly 60% of trials for type 2 diabetes medications registered at clinicaltrials.gov had at least one fertility‐related exclusion criterion; 7% had exclusions for women with child‐bearing potential . Patients with complex comorbidities are also often excluded from trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, even when not explicitly excluded, women remain under‐represented, in part due to fertility‐related exclusions. Although diabetes is a chronic condition with significant morbidity that affects men and women differently, nearly 60% of trials for type 2 diabetes medications registered at clinicaltrials.gov had at least one fertility‐related exclusion criterion; 7% had exclusions for women with child‐bearing potential . Patients with complex comorbidities are also often excluded from trials.…”
mentioning
confidence: 99%
“…Although diabetes is a chronic condition with significant morbidity that affects men and women differently, 4 nearly 60% of trials for type 2 diabetes medications registered at clinicaltrials.gov had at least one fertility-related exclusion criterion; 7% had exclusions for women with child-bearing potential. 5 Patients with complex comorbidities are also often excluded from trials. One report found that although chronic kidney disease is associated with a high risk of death from coronary artery disease and that effectiveness of treatment can be different in this population, 75% of registered trials for drugs to treat coronary artery disease excluded patients with chronic kidney disease.…”
mentioning
confidence: 99%
“…Fourth, the National Institutes of Health and the Food and Drug Administration have issued standards for the inclusion of women of reproductive age in clinical trials . However, coercive policies and language regarding contraception in the consent form may ultimately lead to lower enrollment rates of women or to significant differences between women who choose to enroll in a study and those who do not . Differential enrollment is problematic from a scientific as well as an ethical standpoint.…”
Section: The Problem With Requiring Multiple or Specific Methods Of Cmentioning
confidence: 99%
“…However, this conservative stance enhances neither fetal nor maternal safety. Besides, there is evidence that this risk to the fetus may be overestimated in some studies [30] and that potential benefits may far outweigh this risk in other studies such as gene transfer research [21].…”
Section: Main Textmentioning
confidence: 99%